1998
DOI: 10.1016/s0969-2126(98)00064-1
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with the inhibitory mechanism of serpins: crystal structure of a complex formed between cleaved plasminogen activator inhibitor type 1 and a reactive-centre loop peptide

Abstract: This is the first reported crystal structure of a complex formed between a serpin and a serpin inhibitor. The localisation of the inhibitory peptide in the complex strongly supports the theory that molecules binding in the space between beta strands 3A and 5A of a serpin are able to prevent insertion of the reactive-centre loop into beta sheet A, thereby abolishing the ability of the serpin to irreversibly inactivate its target enzyme. The characterisation of the two binding sites for the peptide inhibitor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 33 publications
5
85
0
Order By: Relevance
“…In contrast, the RCL of latent PAI-1 is fully inserted into β-sheet A (24), stabilizing β-sheet A in a state known as the relaxed conformation (40) with a reported T M of 67.5°C (41). PAI-1 pept is a complex of PAI-1 and an RCL mimicking octapeptide that is bound to β-sheet A in place of an inserted RCL (42), thereby exhibiting structural features of both active and latent PAI-1 (43). Specifically, PAI-1 pept adopts a structurally stable relaxed serpin conformation with a T M of 87.6°C, but contains an exposed RCL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the RCL of latent PAI-1 is fully inserted into β-sheet A (24), stabilizing β-sheet A in a state known as the relaxed conformation (40) with a reported T M of 67.5°C (41). PAI-1 pept is a complex of PAI-1 and an RCL mimicking octapeptide that is bound to β-sheet A in place of an inserted RCL (42), thereby exhibiting structural features of both active and latent PAI-1 (43). Specifically, PAI-1 pept adopts a structurally stable relaxed serpin conformation with a T M of 87.6°C, but contains an exposed RCL.…”
Section: Resultsmentioning
confidence: 99%
“…These movements of the central sheet are similarly required for the insertion of RCL mimicking peptides into sA and for conversion to the latent conformation (24,43,50), and CDE-096 strongly inhibits both peptide insertion and the latency transition. This effect is consistent with a mechanism where CDE-096 binding to the sB/sC pocket stabilizes PAI-1 in a conformation with sA closed at the top.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented in chapter 2 extends these studies using PAI-2 RCL analogues. Recently, the crystal structures of both antithrombin and PAI-1 complexed with synthetic RCL peptides confirmed that the peptides bind as strand 4 of p-sheet A , homologous to the position occupied by the R C L in the relaxed and latent forms of the molecules (Skinner et al 1998, Xue et al 1998.…”
Section: -The P14 Residue (Thr 367 ) Is Critical For R C L Insertion mentioning
confidence: 96%
“…Similarly, detection of RCL binding to PAI-2 using real-time biomolecular interaction analysis (BIAcore) was unsuccessful. Xue et al (1998) have previously demonstrated binding of a short RCL pentapeptide to PAI-1 using BIAcore, however the rate of binding of 14mer RCL peptide to PAI-2 under identical conditions appears to be much slower, making the reaction difficult to interpret by this technique. This interaction is also apparent in the structure of relaxed LEI, where the sidechai (Figure 3.7).…”
Section: Structural Changes In the Hinge Region Of Relaxed Pai-2mentioning
confidence: 99%
“…Three structures of cleaved, human PAI-1 variants have been reported (Aertgeerts et al, 1995 (PDB entry 9PAI); Jensen and Gettins, 2008 (PDB entry 3CVM); Dewilde et al, 2009 (PDB entry 3EOX)). In addition, crystal structures of human PAI-1 variants were elucidated in which PAI-1 is complexed with an inhibiting pentapeptide (corresponding to P14-P10) (Xue et al, 1998) (PDB entry 1A7C) or with the somatomedin B domain of vitronectin (Zhou et al, 2003) (PDB entry 1OC0).…”
Section: Introductionmentioning
confidence: 99%